PROTOTIPE SISTEM PAKAR UNTUK DIAGNOSIS PENYAKIT INFEKSI SALURAN PERNAPASAN (ISPA) MENGGUNAKAN METODE CERTAINTY FACTOR - Mandiri, Puput Dwi; Hartanti, Dwi; Sari, Aprilisa Arum (Universitas Budi Luhur, 2024)
Respiratory Tract Infection is a condition that triggers inflammation of the upper respiratory tract, such as the nose, throat, sinuses, and airways leading to the lungs. Symptoms such as runny nose, cough, sore throat, nasal congestion, sneezing, and fever appear. Because the symptoms are often similar to other diseases, people with respiratory infections are often unaware of their condition. For this reason, a system that can diagnose respiratory infection symptoms quickly and accurately is needed. By integrating biology and artificial intelligence (AI), a biotechnology expert system for respiratory tract infections was developed. The Certainty Factor method is used to assess the level of confidence in a symptom based on the beliefs of an expert. The system is designed for the general public to receive examination results in the form of percentages, which help identify whether the symptoms experienced fall into the category of sinusitis, pneumonia, pharyngitis, or asthma. The doctor's question feature as a development of the previous system, allows users to consult with doctors about the symptoms experienced. The test results that have been carried out show that the results are in accordance with manual calculations. In addition, the system accuracy test resulted in an accuracy value of 80%.